Comportamento, produção e qualidade do leite de vacas Holandês-Gir com climatização no curral - de Almeida, Gledson L. P. (2013)
This study was conducted with the objective to evaluate the duration of exposure of animals to the evaporative cooling system in the waiting barn on the weather variables (temperature and relative humidity), animal behavior, production and quality aspects of milk from Girolando cows. Sixteen multiparous lactating cows were used having a genetic composition of 7/8 Holstein-Gir and mean milk production of 18 kg animal-1day-1. A 4 × 4 Latin square design was used. The experiment was conducted during the summer season (February-March 2009) and lasted 56 days. The treatments consisted of different periods of 10, 20 and 30 minutes of exposure to acclimatization and control. Time of 30 minutes of exposure to thermal conditioning system enabled the second milking (evening shift), providing an increase in milk production in the next milking of 0.640 kg animal-1. A higher percentage of time spent on food intake and rumination (17.31 and 30.19%) in 30 minutes treatment, compared to control (15.50 and 27.37%), respectively. There was no significant effect of treatments in the composition of milk.